Modified frenectomy technique to eliminate the aberrant labial frenum - A report of two cases - Asmita Saokar; Santhosh Kumar; G Subraya Bhat; Adel Sulaiman M. Alagl (Wolters Kluwer Medknow Publications, 2022)
Introduction: A modified frenal treatment for aberrant frenum is presented in this report to reduce scar tissue formation and maintain the attached gingiva. Description: The case report describes two cases in which a V-shaped incision removed the aberrant frenum and then the flaps of the frenum were sutured at the mid line. Results: The results showed reduced scar tissue in the mid line and the tissue healed with adequate attached gingiva. Take-Away Lessons: The modified frenotomy technique presented here is ideal for a large frenum that could expose the underlying connective tissue that could reduce the scar tissue formation.